Konseling Posisi Menyusui yang Baik dan Benar sebagai Persiapan Kesuksesan Ibu dalam Menyusui - Triana, Kornelia; Wea, Kristina Lola; Madur, Junita Putriwan; Naus, Kristiani K. S.; Kurniati, Korenlia; Emel, Kristina A; Jaun, Kristina H; Jita, Karolina G; Idis, Kresensia J.; Trisnawati, Reineldis E. (Pakis Journal Institute, 2025)
Correct breastfeeding position is one of the key elements for successful breastfeeding. However, many postpartum mothers face challenges in breastfeeding due to lack of understanding and skills regarding correct breastfeeding techniques. This study aims to evaluate the effect of counseling on breastfeeding positions in improving postpartum mothers' knowledge. This study used a quantitative design with a pre-experimental approach through the same group before and after the intervention. The sample consisted of 20 postpartum mothers who were selected purposively in the Cancar Health Center work area. The tool used in this study was a multiple-choice questionnaire that had been tested for validity and reliability. The results of the pre-test showed that 65% of respondents had low knowledge, 25% were sufficient, and 10% were good. After being given counseling, there was an increase in knowledge, with 70% of respondents in the good category, 25% were sufficient, and only 5% were lacking. This finding indicates that counseling significantly improves postpartum mothers' knowledge regarding breastfeeding positions. Counseling that is carried out face-to-face and equipped with demonstrations can increase mothers' insight, thus contributing to successful breastfeeding.